Characterization of Centella Asiatica L. leaves by using oven-dried method: article - Zahari, Muhammad Afifuddin; Md Zaki, Nurul Asyikin; Abd Hashib, Syafiza (2019)
This research is mainly to produce dried Centella Asiatica L. (CAL) powder through oven-dried. Since there are no reviews regarding on characterization of CAL that using this method, therefore this research will cover an overview on physicochemical properties on CAL powder by oven-dried and study the effect of temperature on drying rate, moisture content, color and antioxidant activity on methanol. Drying is the way toward removing water from a sustenance item which is practiced by heat. The result showed that as the drying temperature increased, the percentage of moisture content decreased. At temperature 40°C and 80°C the value of total color difference and pH were ∆E=53.90, pH=7.07 and ∆E=50.54, pH=5.92 respectively, so the higher the drying temperature the lower the value of total color difference and pH. Result showed that temperature effect the drying rate, time taken, moisture content, color and antioxidant of CAL.